Molecular rearrangements of superelectrophiles - Klumpp, Douglas A. (Beilstein Journal of Organic Chemistry, 2011)
Superelectrophiles are multiply charged cationic species (dications, trications, etc.) which are characterized by their reactions with weak nucleophiles. These reactive intermediates may also undergo a wide variety of rearrangement-type reactions. Superelectrophilic rearrangements are often driven by charge–charge repulsive effects, as these densely charged ions react so as to maximize the distances between charge centers. These rearrangements involve reaction steps similar to monocationic rearrangements, such as alkyl group shifts, Wagner–Meerwein shifts, hydride shifts, ring opening reactions, and other skeletal rearrangements. This review will describe these types of superelectrophilic reactions.
Keywords: dication; rearrangement; superacid; superelectrophile